DOT1L inhibition does not modify the sensitivity of cutaneous T cell lymphoma to pan-HDAC inhibitors in vitro - Kwesi-Maliepaard, Eliza Mari; Malik, Muddassir; van Welsem, Tibor; van Doorn, Remco; Vermeer, Maarten H.; Vlaming, Hanneke; Jacobs, Heinz; van Leeuwen, Fred (Frontiers in Genetics, 2022)
Cutaneous T-cell lymphomas (CTCLs) are a subset of T-cell malignancies presenting in the skin. The treatment options for CTCL, in particular in advanced stages, are limited. One of the emerging therapies for CTCL is treatment with histone deacetylase (HDAC) inhibitors. We recently discovered an evolutionary conserved crosstalk between HDAC1, one of the targets of HDAC inhibitors, and the histone methyltransferase DOT1L. HDAC1 negatively regulates DOT1L activity in yeast, mouse thymocytes, and mouse thymic lymphoma. Here we studied the functional relationship between HDAC inhibitors and DOT1L in two human CTCL cell lines, specifically addressing the question whether the crosstalk between DOT1L and HDAC1 observed in mouse T cells plays a role in the therapeutic effect of clinically relevant broad-acting HDAC inhibitors in the treatment of human CTCL. We confirmed that human CTCL cell lines were sensitive to treatment with pan-HDAC inhibitors. In contrast, the cell lines were not sensitive to DOT1L inhibitors. Combining both types of inhibitors did neither enhance nor suppress of the inhibitory effect of HDAC inhibitors on CTCL cells. Thus our in vitro studies suggest that the effect of commonly used pan-HDAC inhibitors in CTCL cells relies on downstream effects other than DOT1L misregulation.